1990
DOI: 10.1007/bf00010653
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient uptake by potato crops grown on two soils with contrasting physical properties

Abstract: Potatoes were grown on two contrasting soils but in adjacent sites to investigate the effect of soil type on tuber production, nutrient uptake and nutrient inflow rates (uptake rate per unit length of root). The year of the study was wetter than normal. Tuber growth, root growth and nutrient uptake were all greater on the coarse rather than the fine-textured soil. However there was no difference in nutrient inflow rates between plants growing in the two soils. Therefore, it was concluded that the crop on the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…Meanwhile when compared in the same study, beetroot was found to grow deeper than 1.5 m depth in both sandy loam and coarse sand (Hefner et al, 2019). In our present study, due to the similar bulk densities of two soils in the greenhouse experiment, the deeper rooting depth and higher root intensity of fodder radish growing in sandy loam than in loamy sand soil might not be ascribed to mechanical impedance, aeration, or soil hydraulic conductivity, factors that have been identified in other studies as causing differences in root growth among soil types (Mackie-Dawson et al 1990;Tennant et al 2001). Some possible explanations for difference in root growth could be ascribed to differences in clay content.…”
Section: Effect Of Soil N Availability On N Uptakesupporting
confidence: 58%
See 1 more Smart Citation
“…Meanwhile when compared in the same study, beetroot was found to grow deeper than 1.5 m depth in both sandy loam and coarse sand (Hefner et al, 2019). In our present study, due to the similar bulk densities of two soils in the greenhouse experiment, the deeper rooting depth and higher root intensity of fodder radish growing in sandy loam than in loamy sand soil might not be ascribed to mechanical impedance, aeration, or soil hydraulic conductivity, factors that have been identified in other studies as causing differences in root growth among soil types (Mackie-Dawson et al 1990;Tennant et al 2001). Some possible explanations for difference in root growth could be ascribed to differences in clay content.…”
Section: Effect Of Soil N Availability On N Uptakesupporting
confidence: 58%
“…Root distribution at depth has been shown to be related to soil type. Soil texture is assumed to affect root development because soil properties, such as clay content, soil resistance and porosity, appear to influence root growth (Breuning-Madsen 1985;Mackie-Dawson et al 1990;Tennant et al 2001). For example, roots of chicory (Cichorium intybus) were found to reach to 2.5 m in sandy loam (Thorup-Kristensen 2006), whereas roots only grew to 0.75 m depth in coarse sand (Askegaard and Eriksen 2007).…”
Section: Introductionmentioning
confidence: 99%
“…As a rule, it is limited to the vines that are the most important part of the potato used for nutrient diagnostics (Grzebisz et al., 2018; MacKay, Carefoot, & Entz, 1987). There is not much data available on the nutrients that support N in its impact on tuber yield development, such as P, K, and Mg (Mackie‐Dawson, Millard, & Robinson, 1990).…”
Section: Introductionmentioning
confidence: 99%